Therapeutic inhibition of prolyl hydroxylase domain-containing enzymes in surgery: putative applications and challenges - Harnoss JM (Hypoxia, 2015)
Jonathan Michael Harnoss, Moritz Johannes Strowitzki, Praveen Radhakrishnan, Lisa Katharina Platzer, Julian Camill Harnoss, Thomas Hank, Jun Cai, Alexis Ulrich, Martin Schneider Department of General, Visceral and Transplantation Surgery, University of Heidelberg, Heidelberg, Germany Abstract: Oxygen is essential for metazoans to generate energy. Upon oxygen deprivation adaptive and protective pathways are induced, mediated by hypoxia-inducible factors (HIFs) and prolyl hydroxylase domain-containing enzymes (PHDs). Both play a pivotal role in various conditions associated with prolonged ischemia and inflammation, and are promising targets for therapeutic intervention. This review focuses on aspects of therapeutic PHD modulation in surgically relevant disease conditions such as hepatic and intestinal disorders, wound healing, innate immune responses, and tumorigenesis, and discusses the therapeutic potential and challenges of PHD inhibition in surgical patients.Keywords: hypoxia, HIF, PHD, PHI, surgery